Review article circadian disruption in pathophysiology of diabetes mellitus - Yu. V. Bykov (Фундаментальная и клиническая медицина)
Diabetes mellitus is a leading endocrine disease with a steadily increasing incidence, and its complications impose a heavy burden on the healthcare. Although pathophysiology of diabetes mellitus has been extensively investigated through the recent decades, the role of circadian rhythms in this regard was vaguely described. Circadian rhythms comprise an autonomous system of neuroendocrine signals and transcription factors that enfold key physiological processes into a daily cycle. Circadian clocks are subdivided into central (located in the suprachiasmatic nuclei of the hypothalamus) and peripheral oscillators (located in organs and cells) which produce circadian variations in the activity of virtually all cells within the human body, including the β cells of the pancreas. Circadian rhythm disruption causes circadian desynchronization which is associated with impaired glucose metabolism and insulin secretion, thereby being considered as one of the triggers of diabetes mellitus. Production of melatonin, a master regulator of circadian rhythms and a potent antioxidant, is significantly reduced in patients with diabetes mellitus. Circadian desynchronization may be triggered by a jetlag or an eating disorder. At present, circadian disruption is viewed as an important cause for the development of diabetes mellitus, although the mechanisms of such link have not been fully elucidated hitherto and might include genetic predisposition and increased oxidative stress. Timely diagnosis and appropriate treatment of circadian disruption in patients with diabetes mellitus may ameliorate the severity or prevent diabetes complications.